2022
DOI: 10.3168/jds.2021-21187
|View full text |Cite
|
Sign up to set email alerts
|

A high-concentrate diet provokes inflammation, endoplasmic reticulum stress, and apoptosis in mammary tissue of dairy cows through the upregulation of STIM1/ORAI1

Abstract: High-concentrate feeding can induce subacute ruminal acidosis, which leads to mammary tissue injury in dairy cows. Therefore, the purpose of this research was to evaluate the effect of high-concentrate feeding on STIM1 (stromal interaction molecule 1)/ORAI1 (Orai calcium release-activated calcium modulator 1)-mediated inflammation, endoplasmic reticulum stress (ERS), and apoptosis in the mammary tissue of dairy cows. A total of 12 healthy mid-lactating Holstein cows of similar weight were randomly allotted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…RR036A; Takara) according to the manufacturer's instructions, and then the cDNA was diluted fourfold and used for realtime quantitative PCR (RT-PCR). The primer sequences of STIM1/Orai1 and the genes associated with ERS (PERK, IRE1, ATF6, GRP78, CHOP) were designed using sequence data obtained from the National Center for Biotechnology Information with Primer Premier software 5.0 (Premier Bio soft, California, CA, USA), and the primer sequences of the genes for proinflammatory cytokines (IL-6, IL-8, IL-10, IκB, NF-κB, and TNF-α) were directly obtained from previously published articles [21]. The primer sequences of genes were synthesized in Generay equipment (Shanghai, China), and the details are shown in Table 1.…”
Section: Rna Isolation and Real-time Polymerase Chain Reactionmentioning
confidence: 99%
See 4 more Smart Citations
“…RR036A; Takara) according to the manufacturer's instructions, and then the cDNA was diluted fourfold and used for realtime quantitative PCR (RT-PCR). The primer sequences of STIM1/Orai1 and the genes associated with ERS (PERK, IRE1, ATF6, GRP78, CHOP) were designed using sequence data obtained from the National Center for Biotechnology Information with Primer Premier software 5.0 (Premier Bio soft, California, CA, USA), and the primer sequences of the genes for proinflammatory cytokines (IL-6, IL-8, IL-10, IκB, NF-κB, and TNF-α) were directly obtained from previously published articles [21]. The primer sequences of genes were synthesized in Generay equipment (Shanghai, China), and the details are shown in Table 1.…”
Section: Rna Isolation and Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…LPS can stimulate the immune system and enhance innate immunity at low concentrations, while it causes extensive and intense inflammatory reactions at high concentrations [19,20]. Some studies in the livers of cows have reported that LPS affects the nutrient metabolism of the liver and reduces the immune capacity of animals, and may even cause endotoxemia in serious cases [21,22]. The liver, as the largest digestive organ and immune organ of dairy cows, is one of the main target organs attacked by LPS and plays an important immune role for LPS [22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations